ANALISIS FAKTOR MUAT (LOAD FACTOR) KAPAL PENYEBERANGAN BAKAHUENI – MERAK PADA KONDISI ARUS PUNCAK DAN KONDISI NORMAL - Priangga, Musabiq Ahkmadi; Herianto, Dwi; Sulistyorini, Rahayu (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Transportation consists of facilities and infrastructure to smooth the wheels of the economy, strengthen national unity and integrity and influence almost all aspects of life. One type of transportation is sea transportation which functions to connect people from one island to another by using water transportation such as ships. The purpose of this research is to analyze the loading factor of ships at peak and normal condition and to estimate the number of vehicles at the Bakauheni-Merak ferry port for the next three years. The research method for collecting secondary data is by visiting related agencies, as well as calculating ship loading factors and forecasting vehicle productivity using the linear regression analysis method. From the results of the calculation of the load factor in the normal condition of 2017-2019 it produces a load factor value that does not exceed 30% -58%, while in the peak condition of 2017-2019 and 2022 there is a value that exceeds 100%, namely 105% -140%, so it is necessary to increase the number of trips at the Bakauheni-Merak port pier.